Legal Politics of Investigation Authority in Criminal Offences Under the Draft Criminal Procedure Code (RKUHAP) - Panca Sarjana Putra; S.Siagian, Fahrizal; Brimob Ritonga; Saied Firouzfar; Dedi Kurniawan (JUSTISI, 2025)
The aim of investigative research is a pro justisia stage that serves to gather two pieces of evidence to find the perpetrator of a criminal act after an investigation. This process is known as due process of law, which is contained in the Criminal Procedure Code (KUHAP). The renewal of criminal procedure law is to balance the pre-enactment of the 2026 Criminal Law. Therefore, several research objectives were obtained, namely to explain the authority of investigation in criminal acts in the 1981 KUHAP. Then, another objective is to explain the legal policy review related to the authority of investigation in criminal acts based on the Draft National Criminal Procedure Code. The method used in this study is normative juridical research combined with empirical data, through a conceptual approach, a legislative approach, and a case approach. Novelty This study is novel in that criminal procedure law, particularly dominus litis authority, cannot be expanded and the portion of investigation must remain with the state police investigators. This refers to the effectiveness and efficiency of law enforcement and the principles of human rights. The results of this study show that the authority to investigate criminal acts in Law No. 8 of 1981 on Criminal Procedure is vested in the Indonesian National Police. The legal policy review regarding investigative authority in criminal cases based on the Draft National Criminal Procedure Code aims to prioritize the prosecutorial authority of the public prosecutor in the handling of criminal cases. However, this situation may lead to undesirable issues in the future, such as violations of human rights and the inefficiency of the criminal justice process. The conclusion of this study is that the expansion of the authority of public prosecutors as criminal investigators is dangerous. Therefore, in terms of efficiency, effectiveness, and the enforcement of human rights, the expansion of the authority of public prosecutors in investigations under the Draft Criminal Procedure Code has the potential to undermine the sense of legal justice.